Analysis of Students’ Creative Thinking Skills and Learning Motivation in Science Subjects at State Primary School - Utomo, Rachmat Karno; Roshayanti, Fenny; Nizaruddin, Nizaruddin; Hayat, M Syaipul (Universitas Lambung Mangkurat, 2024)
Teachers have to offer learning opportunities that encourage the development of students, given the students’ relatively limited creative thinking skills and motivation to learn. This study aims to identify the categories of creative thinking skills and learning motivation exhibited by students in relation to each indicator within the field of electrical engineering. This study employed a quantitative descriptive approach, with a sample size of 27 students from 6 grades of SD Negeri Mangkang Kulon 02 Semarang in the 2023/2024 academic year. The data were obtained through the observation guidelines, questionnaires and document analysis, which the researchers meticulously prepared and developed. Based on the descriptive qualitative analysis, the overall rating for creative thinking skills was 68.94%, indicating a moderate level of proficiency. In the descriptive qualitative analysis, each creative thinking skills indicator achieved a maximum of 80.55%, which was classified as high, while the minimum was 60.19%, which was categorized as low. The overall motivation of the students was found to be 72.66%, which is classified as high motivation. The maximum percentage of students' motivation to learn was 79.26%, classified as high motivation, while the minimum percentage was 60.00%, considered sufficient motivation. The results of this study indicate that students at SD Negeri Mangkang Kulon 02 Semarang exhibit low levels of creative thinking skills and moderate levels of motivation in electrical engineering.